1992
DOI: 10.1007/bf01291821
|View full text |Cite
|
Sign up to set email alerts
|

A study of high spin states in the transitional nucleus90Mo

Abstract: The reaction 58Ni(36Ar, 4p)9~has been studied at a beam energy of 149 MeV. A detector array consisting of the OSIRIS spectrometer (12 Compton-suppressed Ge detectors), four charged-particle AE detectors and seven NE-213 neutron detectors at the VICKSI accelerator in Berlin has been used to measure the gamma radiation in 77-and particle-77-coincidence mode. An additional Ge detector was placed at 162 ~ to the beam direction to provide information on DCO ratios. The level scheme of 9~ has been extended up to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Most of the other transitions show RDco~0.5 which is the expected value for a stretched dipole transition. As Kabadiyski et al [2] have shown in their studies on 9~ with the same experimental setup, a A I= 0 dipole transition should have RDco,~ 1.0, which causes difficulties in separating them from stretched E2 transitions. These authors also stated that the DCO-ratios for this setup tend to decrease for small transition energies (Ey < 300 keV) because of different timing properties of the Ge detectors.…”
Section: Dco-ratios Y-ray Angular Distributions and Spin-parity Assimentioning
confidence: 91%
See 4 more Smart Citations
“…Most of the other transitions show RDco~0.5 which is the expected value for a stretched dipole transition. As Kabadiyski et al [2] have shown in their studies on 9~ with the same experimental setup, a A I= 0 dipole transition should have RDco,~ 1.0, which causes difficulties in separating them from stretched E2 transitions. These authors also stated that the DCO-ratios for this setup tend to decrease for small transition energies (Ey < 300 keV) because of different timing properties of the Ge detectors.…”
Section: Dco-ratios Y-ray Angular Distributions and Spin-parity Assimentioning
confidence: 91%
“…Our recent detailed investigations on the eveneven nuclei SSMo and 9~ [1,2] have, indeed, given evidence that the positive-parity yrast states can be surprisingly well explained within this restricted shell model space, up to the highest spins observed, e.g. 24 h in 88Mo [ 1 ].…”
Section: Motivationsmentioning
confidence: 93%
See 3 more Smart Citations